If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(2x-3)=4(x-7)
We simplify the equation to the form, which is simple to understand
-3(2x-3)=4(x-7)
Reorder the terms in parentheses
+(-6x+9)=4*(x-7)
Remove unnecessary parentheses
-6x+9=+4+*(+x-7+)
Reorder the terms in parentheses
-6x+9=+(+4x-28)
Remove unnecessary parentheses
-6x+9=+4x-28
We move all terms containing x to the left and all other terms to the right.
-6x-4x=-28-9
We simplify left and right side of the equation.
-10x=-37
We divide both sides of the equation by -10 to get x.
x=3.7
| 4(6x+2)=8(3x+1) | | .03x+.12(20)=.06+20+x | | 0.03=0.01+2.9 | | x^2-14x=-46 | | 46+12x=17x | | 1.2+12.2= | | 6x^2-38=0 | | -12+a=4 | | abc+dbc= | | 6T-20=-21+5T | | P(x)=-x^2+10x-22 | | q^2-9=0 | | 3(w-4)-2(w-10)=15 | | 4M-9=-3+6M | | 4x-11=6x+10 | | 0=16t^2+64t+8 | | 7(c+4)whenc=8 | | 2-3x-4=10 | | 8x+5=2(3x+1) | | 6a-2whena=7 | | -x+3=3x^2-8x+5 | | 0=12-P^2-Q | | f=9/5(-12)+32 | | 10-29u+10u^2=0 | | 4y-4(5y-5)=2-4(-2-y) | | 9x-3-2=6.8+8x | | f=9/5(43)+32 | | Q=12-P^2 | | -3(t-2)+20=2(t+3) | | 14b+31=15-2b | | 7ax^2+21x^2= | | 2(-m+10s)= |